German railroads, Jewish souls : the Reichsbahn, bureaucracy, and the Final solution /: the Reichsbahn, bureaucracy, and the Final solution. (2020) - Browning, Christopher R; Hilberg, Raul, 1926-2007; Hayes, Peter, 1946 September 7
No abstract available